A Review on Performance Analysis of PDE based Anisotropic Diffusion Approaches for Image Enhancement - Thakur, Niveditta; Khan, Nafis Uddin; Sharma, Sunil Datt (Informatica, 2021)
Partial differential equation based anisotropic diffusion techniques are used extensively in computer vision for image enhancement and edge detection. Anisotropic Diffusion which is found to be a low computational complexity approach which has overcome the undesirable effects of linear smoothing filters and now is popular in prominent research areas of enhancing the quality of low contrast images and speckle noise reduction from geological, industrial and medical images. This paper presents a comprehensive survey on various state-of-the-art anisotropic diffusion techniques for image enhancement. The capability of anisotropic diffusion for enhancing the quality of low contrast images and speckle noise reduction from medical images are further explored. Various objective image quality measures are studied which are used to validate the performance of enhancement approaches. The major research issuesand possible future scopes in this diffusion filtering approach are also discussed.